The spiritual life and educational philosophy of Lord Lytton. Issue 6 (2nd November 2021) - Howlett, John
ABSTRACT: This article addresses the life and educational thinking of Victor Lytton, second Earl of Lytton, who not only involved himself in a wide number of social causes but was instrumental in contributing to the development of progressive education in the early decades of the twentieth century. This he did through his work with the New Ideals in Education conferences but also as he became embroiled with Homer Lane and the Little Commonwealth. Lytton also write a number of books that developed a new theory of education. Drawing upon the archives held at Knebworth House, the paper seeks to explore Lytton's life and thought both by exploring his involvement with various causes but also by a close textual reading of his unique educational philosophy, which appeared as a combination of Christ and Freud. By so doing it seeks to reintegrate Lytton as a significant figure in the progressive educational tradition.